Elevated gut microbiota metabolite bile acids confer protective effects on clinical prognosis in ischemic stroke patients - Wang, Zhaobin; Li, Jing; Xu, Yingxin; Liu, Ye; Zhang, Zhe; Xu, Qin; Lin, Jinxi; Jiang, Yong; Wang, Yongjun; Jing, Jing; Wang, Anxin; Meng, Xia (Frontiers in Neuroscience, 2024)
Background: There is evidence of an association between the gut microbiota and progression of stroke. However, the relationship between gut microbial metabolites, specifically bile acids (BAs), and post-ischemic stroke disability and poor functional outcomes remains unexplored.Patients with acute ischemic stroke (AIS) or transient ischemic attack (TIA) in the Third China National Stroke Registry were grouped according to total bile acid (TBA) quartile on admission.Association of TBA with disability and poor functional outcomes were evaluated using logistic regression models and restricted cubic splines.Results: Data for 9,536 patients were included. After adjusting for confounders, the risks of disability and poor functional outcomes were significantly lower in the highest TBA quartile than in the lowest TBA quartile at the 3-month follow-up, with respective odds ratios (ORs) of 0.65 (95% confidence interval [CI] 0.55-0.78; P < 0.001) and 0.66 (95% CI 0.55-0.78, P < 0.001). Each standard deviation increase in the TBA level reduced the risks of disability and poor functioning outcomes by 10% (adjusted ORs 0.9 [95% CI 0.83-0.98; P = 0.01] and 0.9 [95% CI 0.83-0.97; P < 0.001], respectively). This association remained similar at the 1-year follow-up. After stratification by TOAST subtype, the risk of disability or a poor functional outcome in patients with the large-artery atherosclerosis or "other" subtype was significantly lower in the highest quartile than in the lowest quartile (P < 0.05).Serum TBA is an independent risk factor for disability and poor functional outcomes after AIS or TIA, and exerts a protective effects on brain.